Knowledge and Understanding of Hazardous Waste by Community Participation of Khoksa-ad sub-district Administrative Organization, Khongchai district, Kalasin Province - Nuasri, Chompoo; Kudthalang, Nukool; Sombatyotha, Cherdchai; Senajuk, Watchara; Trisupakitti, Somsuk (วารสารวิจัย มทร. กรุงเทพ, 2019)
The aims of this study were: (1) to examine the amount of heavy metals i.e. lead, mercury, copper, cadmium, manganese contaminated in soil in the area of junk shops in 12 villages of Khoksa-ad sub-district, Khongchai district, Kalasin province, and to assess the quality of groundwater and soil surface water, and measure pH and conductivity of soil and water samples. (2) to investigate hazardous waste disposal in the area of Khoksa-ad sub-district, Khongchai district, Kalasin province. The data were collected and employed the distribution of 329 copies of questionnaire the respondents. The findings revealed that (1) the average amount of heavy substances i.e. lead and cadmium indicated the undetectable value in water quality. (2) majority of the respondents accounting for 223 people or 67.8% knew hazardous waste, 213 people or 64.7% realized the effect of hazardous waste, 246 people or 74.8% did not attend training on hazardous waste. The participation in hazardous waste management was at moderate level (x̄ = 3.29). The people expressed their suggestions on that that sub-district administrative organization should provide waste bin and collecting truck in the area. They also would like the authority to handle hazardous wastes separation and disposal appropriately.